Heavy metal removal from wastewater in fluidized bed reactor - Zhou, Ping; Huang, Ju-Chang; Li, Alfred W.F; Wei, Shirly (Water research (Oxford), 1999)
An innovative process for removing heavy metals including Cu, Ni and Zn from industrial wastewater has been developed. The new technology was based on inducing the nucleated precipitation of heavy metals on the sand surface in a fluidized bed reactor. The results showed that pH had a great effect on heavy metal removal efficiency and the optimum pH was about 9.0 to 9.1. At this pH value, heavy metal removal efficiency could be achieved above 92 and 95% when influent heavy metal concentrations were 10 and 20 mg/l, respectively. When pH was greater than 8.7, above 92.4% of the precipitation was composed of metal hydroxide. Hydraulic retention time (HRT) had almost no effect on heavy metal removal efficiency when HRT was greater than 7.1 min. Scanning electron microscope (SEM) analysis indicated that carbonate injection with a drip-wise manner was more conducive than that with a slug dosing manner for precipitation to be coated on the sand surface.